Identity and Nation in Kazuo Ishiguro's An Artist of the Floating World - Tellini, Silvia [UNESP] (Flinders Univ, Humanities Research Centre, 2018)
An Artist of the Floating World (1986) looks back to Ishiguro's first novel, A Pale View of Hills (1982) and anticipates his third, The Remains of the Day (1989). The painter Ono worries about a possible interference in his daughter marriage negotiations as a consequence of his support to the nationalist government, which compels him to undertake a self-evaluation of his career. By focusing on the Americanisation of the Japanese culture and the generational gap created during the postwar period in Japan, the present article discusses universal conflicts that emerge from verticalised familial and social relationships through the lens of Ono who is having trouble dealing with his sense of guilt and internal conflict regarding his active participation as a nationalist propagandist artist of the empire during the war. His reminiscing reveals mechanisms of self-deception and repression to bury intolerable and unwelcome memories insofar as they are discussed against the backdrop of a unique fluid historical moment of intense upheaval and cultural change in Japan.
Keywords: Kazuo Ishiguro; An Artist of the Floating World; memory; identity; World War II